Women's rights and religious law: domestic and international perspectives - Banda, Fareda; Joffe, Lisa Fishbayn (Law and religion, 2016)
Culture, religion and women's international human rights / Frances Raday -- Marriage, religion and gender equality / John Eekelaar -- Gender, religion and human rights in Africa / Fareda Banda -- Implications of the Vatican commitment to complementarity for the equality of the sexes in public life / Mary Anne Case -- Between strict constructionist sharia and protecting young girls in contemporary northern Nigeria : the case of child marriage (ijbar) / Sarah Eltantawi -- Family law reform, spousal relations, and the "intentions of Islamic law" / Celene Ibrahim -- The woes of WoW : the Women of the Wall as a religious social movement and as a metaphor / Pnina Lahav -- Religious coercion and violence against women : the case of Beit Shemesh / Sima Zalcberg Block -- The impact of "foreign law" bans on the struggle for women's equality under Jewish law in the United States of America / Lisa Fishbayn Joffe -- Systemic misunderstanding between rabbinical courts and civil courts : the perspective of an American rabbinical court judge / Aryeh Klapper -- Socio-legal gendered remedies to get refusal : top down, bottom up / Yael Machtinger -- Challenging stereotypes : gender sensitive- imams and the resolution of family disputes in Montreal / Anne Saris